Study of Consumer Satisfaction Levels with E-Pharmacy Services Using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) - Mabrurotul Mustafidah; Rurynta Ferly Shavira; Rania Adhamira; Annisa Putri Kinanti; Kinanti Citraningsih (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
E-pharmacy is one of the efforts to improve pharmaceutical services to make them easier and more efficient. Customer Satisfaction Index (CSI) is a scale that can describe consumer satisfaction with a product or service. Customer satisfaction with e-pharmacy services can be assessed by the value of customer expectations for service quality and the reality of the service performance received. This study aims to examine the level of consumer satisfaction, expectations, and priorities for attribute improvement in the dimensions of e-pharmacy services so that service providers can evaluate and improve their services. Furthermore, the analytical method in this study uses an analysis of the results of the gap based on the Service Quality (Servqual), Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results of this study indicate that attributes' performance on the dimensions of e-pharmacy services is not satisfactory. Customer satisfaction in e-pharmacy service is 86.11% or in the 'very satisfied' category. Meanwhile, the service attribute prioritized for service providers is to improve the guarantee that the drugs given are in good condition (by showing the drug's expiration date).